2023
DOI: 10.1002/ecy.4051
|View full text |Cite
|
Sign up to set email alerts
|

Negative outcomes of novel trophic interactions along mangrove range edges

Abstract: Tropicalization is a phenomenon that is changing the structure of ecosystems around the world. Mangrove encroachment is a particular form of tropicalization that may have cascading consequences for resident fauna in subtropical coastal wetlands. There is a knowledge gap regarding the extent of interactions between basal consumers and mangroves along mangrove range edges and the consequences of these novel interactions for consumers. This study focuses on the key coastal wetland consumers, Littoraria irrorata (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…These studies, each of which are briefly summarized below, evaluated a diversity of response variables, including dietary preferences and food quality, consumer species abundance and biometrics, and changes in ecological community structure. Goeke et al (2021aGoeke et al ( , 2021bGoeke et al ( , 2023 used feeding trials and food quality assays over a one year period to determine how key coastal wetland consumers, the marsh periwinkle (Littoraria irrorata) and mudflat fiddler crabs (Uca rapax), interact with the encroaching black mangrove (Avicennia germinans) in the Gulf of Mexico. They found that Littoraria avoided consuming Avicennia and selectively ingested leaf tissue from a common marsh grass instead, and that both Littoraria and Uca were found to store ~10% less energy when consuming Avicennia.…”
Section: Saltwater Intrusion and Range Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies, each of which are briefly summarized below, evaluated a diversity of response variables, including dietary preferences and food quality, consumer species abundance and biometrics, and changes in ecological community structure. Goeke et al (2021aGoeke et al ( , 2021bGoeke et al ( , 2023 used feeding trials and food quality assays over a one year period to determine how key coastal wetland consumers, the marsh periwinkle (Littoraria irrorata) and mudflat fiddler crabs (Uca rapax), interact with the encroaching black mangrove (Avicennia germinans) in the Gulf of Mexico. They found that Littoraria avoided consuming Avicennia and selectively ingested leaf tissue from a common marsh grass instead, and that both Littoraria and Uca were found to store ~10% less energy when consuming Avicennia.…”
Section: Saltwater Intrusion and Range Expansionmentioning
confidence: 99%
“…They found that Littoraria avoided consuming Avicennia and selectively ingested leaf tissue from a common marsh grass instead, and that both Littoraria and Uca were found to store ~10% less energy when consuming Avicennia. Though outside the scope of their study, Goeke et al (2023) note that the pattern of food preference and decreased physiological condition in two taxonomically distinct species may represent a general consequence of mangrove encroachment that is not species-specific, with significant implications for energy flow within these changing ecosystems. In particular, as Spartina alterniflora becomes less common, the attendant decrease in body condition of basal consumers may lead to a reduction in prey availability and destabilization of higher trophic levels (Goeke et al 2023).…”
Section: Saltwater Intrusion and Range Expansionmentioning
confidence: 99%